Care : a communication and relationship education primary prevention social cognitive model aimed at developing the self-efficacy of adolescents to verbally respond to sexual coercion - McGinn, Marion (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2017)
This thesis describes the design, development, implementation and evaluation of CARE, a communication and relationship education, primary prevention social cognitive model aimed at developing the self-efficacy of adolescents to verbally respond to sexual coercion. CARE encompasses three components: a CARE pedagogy, a CARE training course and a CARE virtual world. Using a quasi-experimental approach, the main objective of this study was to compare the effectiveness of role-play training in a VW to face-to-face training in a traditional classroom, on the perceptions of adolescents’ towards their assertiveness skills and self-efficacy to respond verbally to sexual coercion. To support the participants to acquire the skills to assertively respond to sexual coercion an integration of Kolb’s learning model and Bandura’s model of self-efficacy was employed. Both quantitative and qualitative research methods were employed in this study, providing a triangulation method to collect the data. A total of 46 students participated in the study. Data was gathered through questionnaire measures pre-and post-intervention and through interviews and role-play assessments. The quantitative aspect of the research employed questionnaires to assess whether there was a change in assertiveness and self-efficacy. Qualitative methods were employed to explore the perceptions of the participants and the facilitator towards the social cognitive training model. To analysis the qualitative data, a thematic analysis approach was taken. The salient findings of this study are as follows: The results showed that the effects of the VW role-play training were comparable to those of role-play F2F training. The finding that the VW produced similar results is very promising. Most sexual coercion prevention programs require the use of several resources such as finance and personnel. Delivering instruction through a medium that achieves the same pedagogical goals has important implications for schools who may have limited resources available and need to allocate funds to other areas. In addition, this study confirms that the use of a VW can be an effective tool for role-playing by providing a rich visual context for the role-plays where students can practice skills in a safe environment. Another key finding pertains to the unique characteristics of VWs, specifically’ presence’, and how a sense of presence contributed to the perceptions of the participants towards the verbal quality of their interactions while enacting the role-plays. Such information is likely to have important implications for initiatives to use VWs for assertive communication to prevent adolescent sexual coercion. This study was significant in that it examined the important contemporary issue of adolescent sexual coercion. To the researcher’s knowledge, no salient studies exist that have addressed this phenomenon through the medium of VWs. In sum, the contributions made by this study are: The design, development, implementation and evaluation of an assertiveness course appropriate for 14-15 year old to respond verbally to sexually coercion. -- The design, implementation and evaluation of a VW to teach assertiveness communication to 14-15 year olds to respond verbally to sexual coercion -- Insights into the teaching and learning implications arising from the study -- Complements existing knowledge and evidence base on educational research and practice -- Complements existing knowledge regarding the features of VWs that influences communication -- Provides signposts for future research in this area.
Keywords: Computer Science & Statistics, Ph.D.; Ph.D. Trinity College Dublin